Maximum city Bombay lost and found - Mehta, Suketu (Penguin Books India Pvt. Ltd, 2006)
A native of Bombay, Suketu Mehta gives us an insider's view of this stunning metropolis. He approaches the city from unexpected angles, taking us into the criminal underworld of rival Muslim and Hindu gangs; following the life of a bar dancer raised amid poverty and abuse; opening the door into the inner sanctums of Bollywood; and delving into the stories of the countless villagers who come in search of a better life and end up living on the sidewalks.